(3OQQ GdSeW aj CNHGQ GdSHWs - (3CMeO Hf eMeO GdNhdGfj GdCfOdSj, CHh LYaQ GHf GdGHGQ,J (B433 (3g` s
(3ChdgG (B:s
(3QMeI Gddg hHQcGJg Ydjce Cgd GdHjJ aQhY GdfHhI hGdQSGdI hjfGHjY GdSeGMI GdHSGdI s
(3BNQgG (B:s
(3hjG CSaG CdG JQO JMjI Shi CQL ef WjH eSc jCQL s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B213s
(3eUOQ GbJfGA GdCUd (B:s
(3ef GdNRGfI GdYGeI HeOjfI GdQHGW (B(2071(3c(B) s
Keywords: (3GdJGQjNs